(untitled) (Asian Journal of Medical and Biological Research, 2016)
The purpose of the present investigation was the preparation and evaluation of gastro-retentive floating drug delivery system for anti-diabetic drug metformin hydrochloride that would retain the drug in stomach and continuously release the drug in controlled manner up to a predetermined time leading to improve bioavailability. The microspheres were prepared by oil-in-oil emulsion solvent evaporation technique using ethyl cellulose, methacrylic acid copolymer (Eudragit RS100, Eudragit RSPO and Eudragit RLPO). The dried floating microspheres were evaluated for percentage yield (%), actul drug content (%), drug entrapment efficiency, floating behavior, scanning electron microscopy and in vitro drug release studies. The microspheres were found spherical, porous and free flowing with a size range. Compatibility studies were performed by fourier transform infra-redand (FTIR) and differential thermal analysis (DTA) techniques. The DTA and FTIR data stated that drug and excipient were compatible. In-vitro release kinetics were studied in different mathematical release models following the zero order, Higuchi and Korsemeyer to find out the linear relationship and release rate of drug. The drug might be released by both diffusion and erosion as the correlation coefficient (R2) best fitted with Korsemeyer model and release exponent (n) was 0.45-0.89. In most cases good in vitro floating behavior was observed and a broad variety of drug release pattern was achieved by variation of the polymer which optimized to match target release profile. The developed floating microspheres of metformin hydrochloride may be used in clinic for prolonged drug release in stomach for at least 8 hrs, thereby improving the bioavailability and patient compliance. Asian J. Med. Biol. Res. December 2015, 1(3): 396-405